Effects of ozone pretreatment and operating conditions on membrane fouling behaviors of an anoxic-aerobic membrane bioreactor for oil sands process-affected water (OSPW) treatment. (15th November 2016) - Xue, Jinkai; Zhang, Yanyan; Liu, Yang; Gamal El-Din, Mohamed
Abstract: Two identical anoxic-aerobic membrane bioreactors (MBRs) were operated in parallel for 742 consecutive days for raw and ozonated oil sands process-affected water (OSPW) treatment. The MBRs not only substantially degraded OSPW classical and oxidized NAs, but also demonstrated outstanding membrane fouling control performance (the MBR receiving raw OSPW experienced its first severe fouling with a transmembrane pressure (TMP) of −35 kPa on Day 433). The mild ozonation (30 mg O3 /L) pretreatment of OSPW remarkably enhanced OSPW NA degradation, and improved the MBR's fouling control in terms of prolonged long-term slow TMP growth phase and reduced TMP jump frequency. Ozonation substantially altered the feed water organic composition, reshaped the microbial community (e.g., reduced growth of extracellular polymeric substances (EPS) producers and biofilm formation facilitators), and lowered EPS production and EPS protein/polysaccharides (PN/PS) ratio, consequently leading to the better fouling control. Examination on fouling behaviors at different HRTs of the raw OSPW MBR indicates that HRT also played a role in determining the dominating fouling mechanism during the sharp TMP rise phase. Therefore, the results of this study suggest that the low-dose ozone pretreatment is a good option to enhance organic contaminant degradation and alleviate membrane fouling in the MBR for OSPW treatment. Graphical abstract: Highlights: The anoxic-aerobic MBR demonstrated excellent membrane fouling control performance. Ozonation substantially enhanced OSPW NA degradation and membrane fouling control. Ozone pretreatment reduced growth of bacteria producing EPS. Less EPS and lower EPS PN/PS ratio observed in the ozonated OSPW MBR. HRT influenced the dominant fouling mechanism during TMP jump phase.